Evaluating serum periostin levels in allergic bronchopulmonary aspergillosis. Issue 4 (3rd December 2019) - Tanaka, Jun; Hebisawa, Akira; Oguma, Tsuyoshi; Tomomatsu, Katsuyoshi; Suzuki, Junko; Shimizu, Hiroshige; Kawabata, Yoshinori; Ishiguro, Takashi; Takayanagi, Noboru; Ueda, Soichiro; Fukunaga, Koichi; Taniguchi, Masami; et al.
Abstract :